Impact of different pruning methods of the ’Niágara Branca’ vine cultivated in the region of the Planalto Norte Catarinense - Würz, Douglas André; Maciel, ThaliaAparecida Silva; Schmidt, Eduarda; Kowal, Alcemir Nabir; Almeida, Rabechlt Stange; Jansen, Thuany Levandoski; Farias, Eduardo Virmond Souza; Altmann, Henry Matheus; Steidel, Otavio Frederico Tschoeke; Palinguer, Rodrigo; et al. (Revista de Ciências Agroveterinárias, 2023)
The objective of this work was to evaluate the effect of two winter pruning methods on yield rates and quality of the ’Niágara Branca’ grape grown in the Planalto Norte region of Santa Catarina. The experiment was carried out in the 2019 and 2020 harvests, in a vineyard on the Niágara Branca variety, located in Canoinhas. The treatments consisted of two different pruning systems: short pruning, leaving spurs with two buds, and mixed pruning, leaving canes with four buds and spurs containing two buds for renewal in the following year. Vegetative and productive indices, cluster architecture and technological maturation were evaluated. The pruning method has an influence on the productive and qualitative characteristics of the Niagara Branca vine, and the adoption of mixed pruning results in a greater number of plant-1 branches, a greater number of plant-1 bunches, a greater mass of bunch-1, a greater number of berries cluster-1, and consequently provides an increase in production rates. Plants produced mixed pruning, an average of 5.5 and 11.2 kg plant-1, in the 2018 and 2019 harvests, respectively, while plants supplied to short pruning obtained an average production of 1.9 and 7.2 kg plant-1. which is recommended for the ’Niágara Branca’ vine grown in the Planalto Norte region of Santa Catarina, without compromising the quality of the grape.